KOMUNIKASI PENDEK Perbanyakan Tanaman Artemisia annua secara In Vitro - Rossa Yunita; Endang G. Lestari (Jurnal AgroBiogen, 2008)
Artemisinin, an anti-malarial medicineisolated from the annual wormwood Artemisia annua,has a marked activity against chloroquine-resistant andchloroquine-sensitive strains of Plasmodium falciparum.This compound is useful for treatment of cerebral malaria.An in vitro propagation system for A. annua has been developed.Shoots were induced by culturing seeds of A.annua on a MS medium containing BAP (0, 0.1, 0.3, 0.5mg/l). Shoots were also formed on each seedling culturedon the same medium. Root formations were obtained fromshoots that were subcultured on a MS medium containingIBA (0, 1.0, 1.5, 2 mg/l). The results showed that MS mediumsupplemented with BAP 0.3 mg/l was the best medium forinduction and multiplication of the shoots, while the MSmedium supplemented with IBA (1 mg/l) was good for rootformations.